(3efM GdSejY TQM JdejM GdHOjY HeOM GdTajYs - (3YHO GdQMef Hf CMeO Hf Ydj GdMejOis; (3YHO GdQMef Hf CMeO Hf Ydj GdMejOj GdeUQj,J (B1005 (3g` s ((3Rjf Hf ESeGYjd Hf CMeO GdcQOi GdMfai s)
(3ChdgG (B:s
(3CeG HYO aEf GdYde hHeG RGO Hg ai GdJfhjY Yfge s
(3BNQgG (B:s
(3gPG GdfhY ai BNQ HOjYGJge hHjJ GdhLjg s
(3JcQGQkG CjVkG JMJ Qbe (B126 (3HdGZIs
(3JdejM GdHOjY ddMejOi TQMgG hSeGgG aJM GdHOjY Ke GNJUQ GdTQM hSeGg efM GdSejYs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
Keywords: (3GdHdGZIs